RETRACTED: Case report: A rare case of tumor-to-tumor metastasis: metastatic lobular breast carcinoma to clear cell renal cell carcinoma - Letian Zhang; Pei Yuan; Qi Cao; Jiali Mu; Jianming Ying; Changyuan Guo (Pathology and Oncology Research)
Tumor-to-tumor metastasis is a rare phenomenon. Although renal cell carcinoma is the most common recipient tumor, metastatic lobular breast carcinoma to clear cell renal cell carcinoma is even rarer, with only one case reported to date. We present a 66-year-old female patient with an invasive lobular carcinoma history who was admitted to the hospital with a right renal mass. The patient received partial nephrectomy. The final established diagnosis is lobular breast carcinoma metastasizing to clear cell renal cell carcinoma (ccRCC). Thus, although rare, the simultaneous or consecutive find of a renal mass in follow-up should be carefully evaluated, especially in high-risk patients, including women with an advanced breast cancer history, as in this scenario.